anonymous
  • anonymous
How do you factor -x^3+6x^2-11x+6 ??
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
ok
anonymous
  • anonymous
what is the problem that u r facing elaborate it
anonymous
  • anonymous
i just need to solve it for 0.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
means that u want the RHS TO BE 0 or x be 0
anonymous
  • anonymous
-x^3+6x^2-11x+6=0 and then solve for x
anonymous
  • anonymous
ok
anonymous
  • anonymous
IV JUST WAIT FOR 2minutes
anonymous
  • anonymous
ok
anonymous
  • anonymous
Putting x=1 we will get:
anonymous
  • anonymous
-1 + 6 -11 + 6 = 0
anonymous
  • anonymous
-12 + 12 = 0
anonymous
  • anonymous
so it shows that x-1 is a factor of THE EQUATION
anonymous
  • anonymous
I know the answers are 1 2 and 3. But how do factor this out is my question.
anonymous
  • anonymous
(-x^3 + 6x^2 -11x + 6) * -1 = 0*-1
anonymous
  • anonymous
ok now
anonymous
  • anonymous
x^3 - 6x^2 + 11x - 6 = 0
anonymous
  • anonymous
x^3 = x^2(x-1) +x^2
anonymous
  • anonymous
-6x^2 = -6x(x-1) - 6x
anonymous
  • anonymous
11x = 11 ( x-1) + 11
anonymous
  • anonymous
putting these values in this equation x^2(x-1) - 5x(x-1) + 6(x-1) = 0
anonymous
  • anonymous
(x^2-5x+)(x-1) = 0
anonymous
  • anonymous
(x(x-2) - 3(x-2) ) (x-1) = 0
anonymous
  • anonymous
x-3, x-2, x-1 = 0
anonymous
  • anonymous
x-3 = 0 x=3 x-2 = 0 x=2 x-1 = 0 x=1
anonymous
  • anonymous
SO BYE AND REPLY ME FAST did u got it
anonymous
  • anonymous
yeah thanks
anonymous
  • anonymous
BYE

Looking for something else?

Not the answer you are looking for? Search for more explanations.